PENGARUH ITO, RECEIVABLE TURNOVER, FAT DAN TATO TERHADAP PROFITABILITAS PADA PERUSAHAAN CONSUMER GOODS INDUSTRY YANG TERDAFTAR DI BEI PERIODE 2017-2019 - septiani sridefi (Akuntansi Prima, 2020)
This study aims to determine the effect of ITO,Receivable Turnover,Fat and TATO on Protability in Consumer Good Industry Companies listed on the Indonesia stock Exchange in 2017-2019.The research method used is a quantitative approach.The population used is manufacturing Companies listed on the Indonesia stock Exchange in 2017-2019 with 51 companies.The sample in this study were 24 Companies with certain criteria.The statistical method used is logistic regression analysis using SPSS 25.The result is that Fixed Asset Turnover has an influence on profitability.Inventory Turnover,Receivable turnover and total asset Turnover have no effect on profitability. Keywords : Inventory Turnover, Receivable turnover, FAT, and TATO, profitability